AKUNTABILITAS DAN PENGENDALIAN INTERNAL PADA ORGANISASI NIRLABA (STUDI PADA GBI AMBARAWA) - Arditha Pramesti; Ester Candra Riyandini; David Adechandra Aschedica Pesudo (BAJ: Behavioral Accounting Journal, 2018)
This study aims to analyze financial accountability practices and internal controls conducted in Church organizations. Accountability practices are divided into 3, namely income, expenditure, and assets and internal control over these three issues. The type of this research is qualitative research. This study uses primary data types through interviews, and secondary data through financial statements. The results of this study indicate that the practice of financial accountability in GBI Organizations. Cipto 3 Ambarawa is sufficient and internal control is relatively loose but does not cause fraud.